Development of cross-school-based Fiqh video learning media at Ma Al Mawaddah Warrahmah Kolaka - Rais, Rara Armita; Hartono, Hartono; Asra, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to develop and evaluate the validity, practicality, and effectiveness of video-based instructional media. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation was conducted by two experts assessing content feasibility, language, presentation, and graphic design, resulting in an average score of 3.58, categorized as highly valid. The practicality of the media was measured through observer assessments, achieving 92.5%, indicating ease of use and comprehension by students. Effectiveness testing was carried out using a one-group pre-test and post-test experimental design, yielding an average gain score of 0.62, classified as high. The findings indicate that video-based instructional media effectively enhances students’ comprehension. The study's implications suggest that this media can serve as an innovative learning alternative, but improvements in visual aspects, background sound, and text-image proportion are necessary for optimal performance. Further research is recommended to test this media on a broader population and compare it with other instructional methods. Therefore, the development of video-based learning media should continue to improve interactive and efficient learning experiences.